The Effect of Human Capital on The Socio-Economic Development of Society - Adkhamjonovich, Samadov Tursunboy (Indonesian Journal Publisher, 2024)
In this article, the main factor of the development of modern society is education, health care, professionalism, creativity and scientific and innovative development of information technologies. Any social phenomenon in society appears as an element of the social system, and human capital becomes its main object